PENGGUNAAN MASKOT SEBAGAI BAGIAN DARI CITY BRANDING KOTA MALANG (STUDI KASUS: OSI DAN JI) - Aris Kurnia Wicaksono; Agung Eko Budiwaspada; G. Prasetyo Adhitama (Gestalt : Jurnal Desain Komunikasi Visual, 2021)
In this modern era, cities play an important role in the country's development strategy, urban planners and designers and all stakeholders build a strong image and reputation in order to compete between cities and introduce them to the world for sources of regional cash income. City branding is one of the city's strategies to display uniqueness so that it is easily recognized and as a differentiator between a city. Currently, many cities in Indonesia have implemented a city ​​branding strategy and some have mascots as part of their city ​​branding. Mascot is part of the visualization of city ​​branding which has a role to strengthen brand identity. Malang City is one of the big cities in Indonesia that has implemented a city ​​branding strategy, namely Beautiful Malang. The city of Malang also has a mascot which is part of the city ​​branding of the city of Malang, namely the mascot of Osiji which is the official mascot of the Malang City government. This research is a study that examines the Osiji mascot in terms of its application. This study discusses the use of the Osiji mascot as part of the city ​​branding strategy of Malang City and how the visual perception arises from the application of the mascot. The purpose of this research is to find out the strategy that has been implemented by the Malang city government in applying the Osiji mascot as part of the city ​​branding of Malang City and to know the visual perception created from the application of the Osiji mascot. This research uses descriptive qualitative method. The theory used in this research is Gestalt's theory of visual perception and Anholt's The City Brand Hexagon theory. The final results in this study indicate that the city ​​branding of Malang through Osiji is considered less than optimal so that the popularity of Osiji has not been able to strengthen the positive image of Malang City. The low popularity of the Osiji mascot is due to the application strategy that does not consider the design principles and concepts of city ​​branding.